2016
DOI: 10.1016/j.ultsonch.2016.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of an ultrasonic nanoemulsion formulation of Nigella sativa L. essential oil on human breast cancer cells

Abstract: Nigella sativa L. (NS) is a plant renowned in traditional holistic medicine systems for almost 1400 years because of its remarkable antioxidant, antimicrobial, anti-inflammatory and anti-cancer properties. The essential oil of N. sativa, in particular, possesses these significant biological properties. However, N. sativa essential oil has many insoluble constituents with properties that have not been fully explored. Nanoemulsion-based insoluble formulations are a widely used carrier system for lipophilic mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(98 citation statements)
references
References 41 publications
1
92
0
5
Order By: Relevance
“…A different volatile extract from the seeds obtained with petroleum ether decreased the viability of A549 lung carcinoma cells exposed to concentrations above 0.1 mg/mL, while an alcoholic extract only exhibited toxicity at concentrations equal or higher than 0.25 mg/mL (Al-Sheddi et al, 2014). A nanoemulsion of essential oil was cytotoxic to MCF-7 breast cancer cells in a dose- and time-dependent manner (IC 50 = 82 and 59 μL/mL for 24 and 48 h, respectively; Periasamy et al, 2016). …”
Section: Scientific Evidence and Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different volatile extract from the seeds obtained with petroleum ether decreased the viability of A549 lung carcinoma cells exposed to concentrations above 0.1 mg/mL, while an alcoholic extract only exhibited toxicity at concentrations equal or higher than 0.25 mg/mL (Al-Sheddi et al, 2014). A nanoemulsion of essential oil was cytotoxic to MCF-7 breast cancer cells in a dose- and time-dependent manner (IC 50 = 82 and 59 μL/mL for 24 and 48 h, respectively; Periasamy et al, 2016). …”
Section: Scientific Evidence and Mechanisms Of Actionmentioning
confidence: 99%
“…Thabrew et al (2005) demonstrated that an aqueous extract inhibited DNA (IC 50 = 3 mg/mL) and protein synthesis in HepG2 cells. A nanoemulsion of essential oil caused cell death by either apoptosis (~44% after 24 h) and necrosis (~28% after 24 h; Periasamy et al, 2016). Thymoquinone, the major compound of N. sativa , caused DNA fragmentation, induced apoptosis (36% vs. 2.5% after 48 h), induced the expression of caspase-8 precursor, and downregulated procaspases-3 (Khalife et al, 2016).…”
Section: Scientific Evidence and Mechanisms Of Actionmentioning
confidence: 99%
“…Antimicrobials are among the most commonly purchased drugs worldwide . Health problems demand a novel class of effective antimicrobial compounds to be more resistant against pathogenic microorganisms than the current antibiotics . This goal can be obtained by identifying new drug targets via genomic, improving the existing antibiotics, and most importantly by identifying new antimicrobial agents with novel materials and mode of action .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that the nanoemulsion of NS oil at a concentration of 20-80 µL/mL caused cell membrane blebbing, cytoplasmic vacuolation, marginalization of chromatin, and fragmentation of the nucleus in MCF-7 cells [16]. A recent evidence suggests that topical use of black seed oil (600 mg) reduced cyclic mastalgia in woman (n = 52), where the activity was found significant when compared to the painkiller, diclofenac [17].…”
Section: Ns In Cancermentioning
confidence: 99%